2018
DOI: 10.1136/bmjopen-2017-019370
|View full text |Cite
|
Sign up to set email alerts
|

Association of body flexibility and carotid atherosclerosis in Japanese middle-aged men: a cross-sectional study

Abstract: ObjectiveThis study examined the associations of body flexibility with carotid arterial remodelling, including intima–media thickness (IMT) and plaque formation in middle-aged men.MethodsThe subjects of this cross-sectional study included 1354 Japanese men aged 35–59 years without histories of stroke or cardiac diseases. The arm extensibility test, which can estimate flexibility of the upper extremity (composed of shoulder external rotation and forearm supination), and the sit-and-reach test were performed. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…All 33 studies were either cross-sectional or randomized controlled trials published within the past 10 years (Table 1). Twenty-three studies [20,26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] included healthy mixed-age adults (age range 18-95) and two studies [53,54] included healthy community-dwelling older adults (age range [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Six studies sampled participants with hypertension [55][56][57][58][59][60], one study sampled individuals with diabetes as a comparator to healthy aged popula...…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
See 4 more Smart Citations
“…All 33 studies were either cross-sectional or randomized controlled trials published within the past 10 years (Table 1). Twenty-three studies [20,26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] included healthy mixed-age adults (age range 18-95) and two studies [53,54] included healthy community-dwelling older adults (age range [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Six studies sampled participants with hypertension [55][56][57][58][59][60], one study sampled individuals with diabetes as a comparator to healthy aged popula...…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
“…Study populations varied from a minimum of 6 [20] to a maximum of 3356 [42] participants. Eight studies included only men [25,27,37,42,49,50,56,61] and four studies included only women [38,52,53,60]. Most studies reported the age range of the participants, except for two studies with one claiming to study "middle-aged" adults [46] and one using adult participants [62].…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
See 3 more Smart Citations